Artificial life the quest for a new creation - Levy, Steven 1951- (Pantheon Books, 1992)
This is the startling story of a new science: the science of artificial life. Computer scientists, microbiologists, chemists, physicists, mathematicians, and evolutionary theorists have succeeded in making creatures that look and act very much like living organisms. They grow, eat, reproduce, mutate, fight with each other, die--and do all this spontaneously, without interference from their human creators. Artificial Life is also the story of a new way of doing science, one arising not out of the laboratory but out of the computer. The power of the computer to depict--and create--emerging systems has transformed our understanding of evolution, the origins of life, and the essential dynamics of natural phenomena, enabling scientists to move beyond life-as-we-know-it to life-as-it-could-be. In the hands of a-life researchers, the computer is not merely a tool but a breeding ground. The artificial organisms that emerge will not only perform our labors but will help us crack nature's toughest codes. Eventually, we may come to grant them the autonomy due other living creatures. From one of our premier chroniclers of the computer age, the author of the classic Hackers, comes a dazzling journey into the heart of artificial life: software that utilizes the force of evolution to solve complex problems, insectlike robots designed to pave a landing area for a manned Mars mission, the use of natural selection to "train" molecules to fight the AIDS virus. Steven Levy portrays the scientists and how their dreams and obsessions have led them to a new way of looking at life. By making life, we may finally know what life is.
Keywords: Computersimulaties; Neural networks (Computer science); Künstliche Intelligenz; Künstliches Leben